1995
DOI: 10.1080/00405009508631327
|View full text |Cite
|
Sign up to set email alerts
|

The Torsional Behaviour of Singles Yarns. Part II: Evaluation

Abstract: A theoretical analysis has been developed to gain an insight into the torsional behaviour of singles yams, which may be bulky and which may have non-uniform fibre-packlng-deasity distribution. In this paper, a detailed experimental evaluation of the theory for two different cases of yam torsion is reported whereby its predictions of a torque-twist relationship are compared with results obtained for woollen-spun carpet yarns spun at various twist levels. Also presented are typical theoretical results ofthe rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
2
5
2
Order By: Relevance
“…Figure 10 illustrates that for a comparatively small given pre-tension fiber torsion contributed the most to the total yarn torque and the fiber bending played an important role as well. This observation is different from that of Tandon et al [18] in which the author stated that the contributions to yarn torque due to fiber bending and torsion are negligible. With the increasing of the yarn twist the contributions to yarn torque due to fiber bending and fiber tension become more and more important.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…Figure 10 illustrates that for a comparatively small given pre-tension fiber torsion contributed the most to the total yarn torque and the fiber bending played an important role as well. This observation is different from that of Tandon et al [18] in which the author stated that the contributions to yarn torque due to fiber bending and torsion are negligible. With the increasing of the yarn twist the contributions to yarn torque due to fiber bending and fiber tension become more and more important.…”
Section: Resultscontrasting
confidence: 94%
“…In contrast, all three contributions were significant and important in the torsional model when the pre-tension was comparatively small. This finding is different from that of Tandon et al [18] in which it was concluded that the contributions of both fiber bending and torsion to yarn torque were negligible.…”
Section: Appendix Notationcontrasting
confidence: 99%
See 1 more Smart Citation
“…These formulae are also used below to estimate this order of magnitude. Data given in [13], and more recently in [14], show that the ratio K /B given above is in approximate agreement with their data for textile yarns.…”
Section: The Mathematical Formulationsupporting
confidence: 79%
“…However, the verification of the models of the density distribution of fibers in the yarn cross-section proved the existence of significant differences between the experimental results and the implementation of the model. Tandon et al 16 described a torsion model for yarn, applying the so-called ''energetic method'' to characterize the phenomenon of migration of staple fibers in the yarn (calculation of the work required to stretch the yarn, bend it, and twist) under conditions of uneven distribution of fibers in the yarn's cross-section.…”
Section: Fiber Packing Density In the Yarn Cross-sectionmentioning
confidence: 99%